Pemurnian dan Karakterisasi Enzim Endokitinase dari Agen Pengendali Hayati Trichoderma reesei - Harjono Harjono; S. M. Widyastuti; S. Margino (Universitas Gadjah Mada, 2001)
This experiment was aimed to purify and characterize the endochitinase of Trichoderma reesei. Extracellular endochitinase was produced by T. reesei strain T13, a fungal biocontrol agent in colloidal chitin medium as sole carbon source. The enzyme was purified by ammonium sulfate precipitation, followed by gel filtration chromatography and chromatofocusing. The results showed that T. reesei produced endochitinase with molecular weight of 32 kDa and the activity was optimum at pH of 5,5 and temperature of 30 to 35oC.